2021
DOI: 10.1142/s1758825121500174
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Sub-Step Composite Time Integration Formulation With Enhanced Performance on Linear and Nonlinear Dynamics

Abstract: An improved time integration scheme is proposed for linear and nonlinear dynamics. The proposed scheme has two free parameters which control numerical dissipation and accuracy effectively. Basic properties including spectral stability, algorithmic accuracy, algorithmic damping, period elongation and overshooting behavior are investigated. The influences of algorithmic parameters on these properties are quantified. The effectiveness of the proposed scheme for linear and nonlinear dynamics is evaluated through s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…It is difficult in Equation ( 26) to obtain the analytical expression of š›¾ 1 in terms of šœŒ āˆž 3 . Figure 1A depicts the unconditionally stable region of TSSC, fulfilling Equation (26). For each given šœŒ āˆž 3 āˆˆ (āˆ’1, 1), Equation ( 26) provides the upper and lower…”
Section: (šœŒmentioning
confidence: 99%
See 4 more Smart Citations
“…It is difficult in Equation ( 26) to obtain the analytical expression of š›¾ 1 in terms of šœŒ āˆž 3 . Figure 1A depicts the unconditionally stable region of TSSC, fulfilling Equation (26). For each given šœŒ āˆž 3 āˆˆ (āˆ’1, 1), Equation ( 26) provides the upper and lower…”
Section: (šœŒmentioning
confidence: 99%
“…As reviewed in Section 1, a noticeable number of studies 11,16,19,[23][24][25][26][27][28][29][30][31]33 have reported some composite three-sub-step implicit methods. However, there are some identities among them.…”
Section: Comparisonsmentioning
confidence: 99%
See 3 more Smart Citations